Water acting as a catalyst for electron-driven molecular break-up of tetrahydrofuran - Enliang Wang (Nature Portfolio, 2020)
Reactions induced by low-energy electrons in hydrated systems are central to radiation therapy, but a full understanding of their mechanism is lacking. Here the authors investigate the electron-impact induced ionization and subsequent dissociation of tetrahydrofuran, model for biochemically relevant systems, in a micro-solvated environment.